2021
DOI: 10.1093/narcan/zcab029
|View full text |Cite
|
Sign up to set email alerts
|

VEGFA’s distal enhancer regulates its alternative splicing in CML

Abstract: Enhancer demethylation in leukemia has been shown to lead to overexpression of genes which promote cancer characteristics. The vascular endothelial growth factor A (VEGFA) enhancer, located 157 Kb downstream of its promoter, is demethylated in chronic myeloid leukemia (CML). VEGFA has several alternative splicing isoforms with different roles in cancer progression. Since transcription and splicing are coupled, we wondered whether VEGFA enhancer activity can also regulate the gene’s alternative splicing to cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
1
7
2
Order By: Relevance
“…The demethylation of vascular endothelial growth factor A (VEGFA) enhancer in CML promotes the overexpression of cancer signature genes. A study by Dahan showed that VEGFA+157 eRNA regulates its selective splicing, which affects CML cell proliferation by increasing RNAPII elongation via CCNT2 ( 161 ).…”
Section: Resultsmentioning
confidence: 99%
“…The demethylation of vascular endothelial growth factor A (VEGFA) enhancer in CML promotes the overexpression of cancer signature genes. A study by Dahan showed that VEGFA+157 eRNA regulates its selective splicing, which affects CML cell proliferation by increasing RNAPII elongation via CCNT2 ( 161 ).…”
Section: Resultsmentioning
confidence: 99%
“…VEGF-A variants were differentially expressed in the organoids in hypoxia ( Figures 5A–C ), consistent with previous studies. ( Farina et al, 2020 ) VEGF-A189 was significantly upregulated in organoids cultured in hypoxia, which is associated with microvessel formation ( Li et al, 2004 ; Jagannathan et al, 2016 ) and enhanced migration of endothelial cells ( Dahan et al, 2021 ). Being positively charged in some domains, encoded for by exons 6a, 6b and 7, VEGF-A189 binds negatively charged extracellular matrix and heparan sulphate proteoglycans on cell surfaces, remaining spatially localized and becomes biologically active upon mobilization by heparinase.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated the connection between enhancer activity and alternative splicing (42). The enhancer was demonstrated to promote transcription elongation kinetics to promote exon inclusion.…”
Section: Discussionmentioning
confidence: 99%